2021
DOI: 10.3390/biomechanics1030023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ground Reaction Forces between Combat Boots and Sports Shoes

Abstract: It is unclear whether military shoes (combat boots and sports shoes) attenuate loading rate or affect force transfer during walking. Therefore, this study compared ground reaction forces (GRF) related to impact and force transfer between combat boots, military sports shoes, and running shoes. Ten army recruits walked over a walkway with two force plates embedded. GRF were measured when walking barefoot (for data normalisation) and with combat boots, military sports shoes, and running shoes. Loading rate, first… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Two variables were chosen for analysis: (1) peak force, which was the maximum force value of each step taken, and (2) loading rate, calculated as the slope of vertical GRF from 20% to 80% of the time from initial contact to peak impact force. These types of GRF variables are commonly used to evaluate combat footwear during walking 10…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two variables were chosen for analysis: (1) peak force, which was the maximum force value of each step taken, and (2) loading rate, calculated as the slope of vertical GRF from 20% to 80% of the time from initial contact to peak impact force. These types of GRF variables are commonly used to evaluate combat footwear during walking 10…”
Section: Methodsmentioning
confidence: 99%
“…One possible factor that may influence lower limb injuries is the choice of combat boots 10–13. While combat boots are essential protective gear for military personnel, it has been suggested that the poor shock absorption properties, poor fit and inadequate comfort of combat boots can be possible contributing factors to injuries 1 11.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations